The Activity of Unripe Wood Apple (Limonia acidissima Groff) Peel and Flesh Extracts in Inhibiting Diarrhe-Causing Bacteria - Idar, Idar; Sukmawati, Ika Kurnia; Kurnia, Dewi; Nurjanah, Tina Siti; Hutasoit, Lestari (Chimica et Natura Acta, 2025)
Diarrhea is characterized by having liquid stool more often than usual, typically occurring three or more times within a 24-hour period. While rarely fatal, it can disrupt daily life and is often treated with antibiotics due to pathogens like Bacillus cereus, Shigella flexneri, and Salmonella typhimurium. An overgrowth of Escherichia coli can also be a contributing factor. Recent studies suggest that unripe wood apples may have antibacterial properties. This study evaluates the antibacterial activity of extracts from the peel and flesh of the fruit against the bacteria, as mentioned earlier. Using disk diffusion, microdilution, and bioautography methods, it was found that the ethanol extract inhibited Bacillus cereus and Shigella sonnei, while the flesh extract affected Bacillus cereus and Escherichia coli. The bioautography test, however, showed no antibacterial activity from either extract, likely due to their low concentration. In conclusion, the peel and flesh extracts of unripe wood apples exhibit potential antibacterial activity against diarrhea-causing bacteria, particularly Bacillus cereus.